(untitled) (Sciences & Technology. A, exactes sciences, 2013)
In this paper, numerical modeling and simulation of the thermal behavior of a solar collector vacuum tube with a concentration has been done, the value of adding a system of concentration at the back of the collector and try to increase the amount of solar radiation incident on the collector in order to obtain high temperatures compared to traditional flat plate collector and improved their energy performance, this type of collector being integrated into buildings for domestic hot water, air conditioning and for cooling.